2007
DOI: 10.3748/wjg.v13.i32.4340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E on oxidative stress status in small intestine of diabetic rat

Abstract: The results revealed the occurrence of oxidative stress in the small intestine of diabetic rats. Vitamin E, as an antioxidant, attenuates lipid peroxidation and protein oxidation, and increases antioxidant defense mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 42 publications
7
28
0
7
Order By: Relevance
“…Elsy, et al: Vitamin E and muscle regeneration in diabetics lower in DC, this is in agreement with other studies [30,31]. This activity was normalizing in control group after vitamin E treatment [31].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Elsy, et al: Vitamin E and muscle regeneration in diabetics lower in DC, this is in agreement with other studies [30,31]. This activity was normalizing in control group after vitamin E treatment [31].…”
supporting
confidence: 90%
“…This activity was normalizing in control group after vitamin E treatment [31]. The 3-week administration of d-δ-TRF enhances the serum catalase activity in treated groups [6].…”
mentioning
confidence: 79%
“…The decreased catalase activity in plasma and tissues of STZ-diabetic rats may be due to its increased utilization for scavenging the toxic products of lipid peroxidation or due to decreased availability of H 2 O 2 [49]. Vitamin E treatment has been shown to normal ize the catalase activity in the control group [50]. The result of present study revealed that d-δ-TRF supplementation enhances the serum catalase activity in treated groups.…”
Section: Discussionmentioning
confidence: 46%
“…The present study showed that the serum catalase activity was lower in DC. Many other studies [49,50] stated that the catalase activity had decreased in plasma, liver and kidney of diabetic control rats. The decreased catalase activity in plasma and tissues of STZ-diabetic rats may be due to its increased utilization for scavenging the toxic products of lipid peroxidation or due to decreased availability of H 2 O 2 [49].…”
Section: Discussionmentioning
confidence: 97%
“…The combination of intracellular signaling disorders (De Giorgio & Camilleri, 2004), morphoquantitative and neurochemical changes of enteric neurons may be linked to relevant clinical problems of neurological manifestations of DM. Therapeutic measures are being concentrated in an attempt to prevent and/or reduce the excess of free radicals generated during the oxidative stress, in order to prevent or lessen the neurological diabetes complications (Shirpoor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%